Development time of Aedes aegypti during winter in temperate Argentina - Di Battista, Cristian Matias (2024)
The data correspond to the Development time of females and males of Aedes aegypti from cohorts initiated in late autumn, early winter and mid-winter and under two treatments, sun and shade. The experiment was conducted under natural thermal and nutritional conditions representative of the temperate region of Argentina.